Leisure Time Use and Adolescent Mental Well-Being: Insights from the COVID-19 Czech Spring Lockdown - Cosma, Alina; Pavelka, Jan; Badura, Petr (International journal of environmental research and public health, 2021)
BACKGROUND: As leisure-one of the crucial life domains-was completely disrupted by the COVID-19 pandemic, our study aimed to investigate how adolescents spent their leisure time during the Spring 2020 lockdown. Secondly, we aimed to investigate the associations between the perceived changes in leisure time use, the leisure activities adolescents engaged in, and the associations with well-being during the Spring 2020 lockdown in Czechia. METHODS: Data from 3438 participants were included in this study (54.2% girls; mean age = 13.45, SD = 1.62). First, the initial number of items measuring leisure, electronic media use, and sports was reduced through Principal Component Analysis (PCA). Multivariate linear regression models tested the associations between leisure domains and mental well-being Results: The amount of leisure time, together with socially active leisure and sports and physical activity, formed the strongest positive predictors of mental well-being, whereas idle activities and time spent on electronic media acted as negative predictors. The amount of time spent doing schoolwork was unrelated to mental well-being. CONCLUSIONS: Overall, our results support the idea that leisure as a promoting factor for well-being is not just a matter of its amount but rather of engagement in meaningful and fulfilling activities.
Keywords: kontrola infekčních nemocí; adolescents; Pandemics; volnočasové aktivity; free time; SARS-CoV-2; mladiství; Česká republika; mužské pohlaví; leisure; COVID-19; active leisure; Czech Republic; mental health; Communicable Disease Control; ženské pohlaví; Humans; physical activity; pandemie; Female; Leisure Activities; Adolescent; lidé; Male